2011
DOI: 10.1128/jvi.05360-11
|View full text |Cite
|
Sign up to set email alerts
|

RelA Ser276 Phosphorylation-Coupled Lys310 Acetylation Controls Transcriptional Elongation of Inflammatory Cytokines in Respiratory Syncytial Virus Infection

Abstract: Respiratory syncytial virus (RSV) is a negative-sense single-stranded RNA virus responsible for lower respiratory tract infections (LRTIs) in humans. In experimental models of RSV LRTI, the actions of the nuclear factor B (NF-B) transcription factor mediate inflammation and pathology. We have shown that RSV replication induces a mitogen-and-stress-related kinase 1 (MSK-1) pathway that activates NF-B RelA transcriptional activity by a process involving serine phosphorylation at serine (Ser) residue 276. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
147
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 86 publications
(156 citation statements)
references
References 56 publications
9
147
0
Order By: Relevance
“…RSV replication in airway epithelial cells is a potent trigger of intracellular and endosomal pattern recognition receptors (13)(14)(15)(16). Our work and that of others have shown that cytoplasmic viral genomic RNA is recognized initially by the cytoplasmic retinoic acid-inducible gene I (RIG-I) and later by the endosomal Toll-like receptor 3 (TLR3) (17,18), whose coordinated actions are required for an effective innate immune response (19)(20)(21).…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…RSV replication in airway epithelial cells is a potent trigger of intracellular and endosomal pattern recognition receptors (13)(14)(15)(16). Our work and that of others have shown that cytoplasmic viral genomic RNA is recognized initially by the cytoplasmic retinoic acid-inducible gene I (RIG-I) and later by the endosomal Toll-like receptor 3 (TLR3) (17,18), whose coordinated actions are required for an effective innate immune response (19)(20)(21).…”
mentioning
confidence: 81%
“…In the case of RSV infection, RelA Ser 276 phosphorylation is mediated by the reactive oxygen species (ROS)-inducible RS6K family member MSK1 (mitogen and stress-activated kinase 1) (37). NF-B/RelA Ser 276 phosphorylation is a rate-limiting posttranslational modification necessary for p300/CBP-dependent Lys 310 acetylation and complex formation with BRD4/CDK9 positive transcriptional elongation factor (14). As a result, RelA Ser 276 is a key posttranslational modification controlling immediate early cytokine gene expression by the process of transcriptional elongation (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7A and B). RelA acetylation at Lys310 determines the recruitment of the cellular elongation factor PTEF-b by the binding of the bromodomain 4 (Brd4) protein to obtain full transcriptional processivity by RNA polymerase II (Pol II) (43,44). We speculate that IRF-1, through its ability to promote RelA acetylation at Lys310, may facilitate both PTEF-b recruitment and transcriptional elongation of the IFN-␤ and IL-8 genes.…”
Section: Stimulated Cd4mentioning
confidence: 99%
“…Cell Culture-Human A549 pulmonary epithelial cells (American Type Culture Collection (ATCC)) were grown in F12K medium (Invitrogen) with 10% fetal bovine serum, 100 units/ml penicillin, and 100 g/ml streptomycin at 37°C in a 5% CO 2 incubator as described previously (28).…”
Section: Identification Of Rela-binding Protein By Affinity Tandem Mamentioning
confidence: 99%